Bending Effect on the Single Mode Optical Fibers - Thomas, Nejla P. S.; Hasan, Hasan A.; Al Naimee, Kais A. (Iraqi Journal of Laser, 2005)
Bending effects on the transmission of optical signal are investigated on a single modeoptical fiber (SMOF) of 10 m length, core radius of 5 μm and optical refractive index difference0.003. The bending radii (R) were between 0.08 and 0.0015 m. A great decrease in the amplitude isshown for radii below 0.01 m. Sudden break down occurs for radii less than 0.0015 m. Birefringence(B) is difficult to measure for long fibers. Meanwhile, B was found by comparing with calibratedfiber of the same properties but of length of 0.075 m. The results show an increase in propagationconstant (Δβ) and the decrease in beat length (Lb), and show that bending decreases the critical radiusof curvature (Rc) related to B. The changes induced on the initial phase of the signal are shown forbending curvatures of radii 0.06, 0.03 and 0.005 m. The linear phase retardation is found to increasemore rapidly for bends of R< 0.05 m. The degree of polarization decreases smoothly for bends ofR>0.01m. Below this curvature, the fluctuation and great instability in the polarization- state of theoutput signal are easily detected. All these features are very important in using SMOF in sensitiveoptical devices especially in long distance fiber communications.